O uso da simulação Massa-Mola do PhET como auxílio para a aprendizagem da força elástica (Lei de HOOKE) - Oliveira, Benjamim Nunes de (2016)
The little motivating way to present Physics is one of the reasons why the students are not very interested about it. Therefore, methodological changes are required to enable a more attractive and meaningful way for education. The PhET's mass-andspring simulation enable a greater connection between the analysis of the physical phenomenon theoretically, in the classroom, and the experiments in a virtual lab, because they allow the results to be viewed several times, providing a better understanding of the variables involved. Thus, this work presents a research on the use of this simulation as a way to help students learn the Elastic Force grounded in the idea of the theories of motivation, which is considered by many authors as a force or reason that moves a person or that puts them into action or does change their direction; and the meaningful learning, that the authors consider as a method of interaction between the new concept and the relevant prior knowledge, aiming to prove the effectiveness of this simulation as an important tool to the learning of such content, which should not be considered as a single but one more methodological possibility. A comparison between two groups of the 9th grade of elementary education at a public school in the city of Messiah-AL was carried out in the period from 10.08.2015 to 10.22.2015, where in one of the classes a computer simulation was used and in the other one it was not, in order to check effectively if the use of this simulation can definitely help these students in this perspective. It was verified a significant improvement in some aspects of the students learning with the use of the PhET's mass-and-spring computer simulation, particularly with regard the resolution of problems involving mathematical calculations and in the motivation to study the concept of Elastic Force.